O Parque Cinturão Verde de Cianorte : de fragmentação florestal à área protegida no espaço urbano - Souza, Nadir Leandro de (2015)
The existence of protected natural areas in cities at the same time contributing to the improvement of environmental conditions of urban areas and their populations, establishes restrictions on residents and the urban organism as a whole, on the other hand are pressed and impacted by the city assembly and the actions of its inhabitants. Thus, this study aims to analyze, through a case study, the importance of protected natural areas, specifically protected areas, urban arrangement, ie the environmental objectives of these areas, the effect of these as the prerogatives the expansion of the urban fabric and the aspirations of the population for recreational areas in environmentally protected areas. Two hypotheses were admitted a) the presence of protected natural areas in cities can boost urban planning in line to natural elements and can also interfere with expansion and planning of the urban fabric. (b) Protected natural areas, such as the Green Belt Park, in reality, little welcome the aspirations of residents by leisure facilities in the places where they operate and compromise the conservation objectives bandied about for the area. The empirical study has reference to the Green Belt Park Cianorte in Cianorte, City of Greater Region Northwestern Paraná. The study planning proceeded from literature review on the topic in question; historical characterization of the evolution of the place; analysis of official documents of the city and legislation for protected natural areas and natural heritage. As a result of the research, it can be said that Cianorte, from its original design, was associated with the existence of forest fragments, referring to the English garden city idea; the transforming capacity of human groups on the natural landscape and the consequents truggle for themaintenance of some fractions of this landscape as natural heritage, as record of the history of the place. Also the use of the area by residents is directly related to infrastructure, as in the existing areas in other urban centers analyzed in this study, the population is present in those spaces that offers them some structural conditions. It follows that the empowerment environmental knowledge of Cianorte residents about the specifics of the Park will favor its preservation.